PENGARUH PENGGUNAAN GAME WORDWALL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Moh. Rizal Umami; Mastuti Alawiah; Muakhor Zakaria (JIP: Jurnal Ilmu Pendidikan, 2025)
This research is motivated by low problem solving abilities. The purpose of this research is to determine the effect of wordwall games on problem solving abilities. The research method used in this research is a quantitative method (Quasi Experiment). In this research, researchers carried out random sampling. Based on the research results, it can be concluded that: (1) There is an influence of using the Wordwall Game on students' mathematical problem solving abilities with test results using a simple linear regression test and a one-way ANOVA test with a significance level of 0.05. The simple linear regression test has a significance value (Sig.) of 0.000 < 0.05 so it can be concluded that H0 is rejected and H1 is accepted which shows that "there is an influence of the use of the Wordwall Game on students' mathematical problem solving abilities". (2) The one-way ANOVA test has a significance value of 0.043 < 0.05, so there is a difference in average values. There are differences between students who use the Wordwall Game and students who do not use the Wordwall game regarding mathematical problem solving abilities. With the test results using the Independent Sample t-Test, namely the Sig value. amounting to 0.000 < 0.05 as the basis for decision making in the Independent Sample t-Test test states that H0 is rejected and H1 is accepted, namely that there is a difference between students who use the Wordwall Game and students who do not use the Wardwall game regarding mathematical problem solving abilities.